Parents’ Roles in Overcoming Elementary Students’ Learning Difficulties - Ika Maryani; Noven Kusainun; Laila Fatmawati; Vera Yuli Erviana; Muhammad Nur Wangid; Ali Mustadi (International Journal of Evaluation and Research in Education (IJERE), 2018)
This research aims to identify learning problems and the parents’roles in overcoming learning difficulties of 5th-grade students of Muhammadiyah Karangturi Elementary School, Bantul, Yogyakarta. Research participants were six students with learning difficulties, six parents, and four teachers. Selection of subjects used purposive sampling technique. Research object was the parents’ roles in overcoming students’ learning difficulties. This research was a qualitative research with data collection techniques in the form of observation, interviews, and documentation. Data analysis technique was the interactive model (data collection, data reduction, data models, and drawing conclusions). The results showed that the problems experienced by students with learning difficulties in Muhammadiyah Karangturi Elementary School were lower than average learning outcomes, slow understanding, and lack of reasonable attitudes, behavior, and emotional symptoms during the learning process. The parents’ roles in overcoming students’ learning difficulties are finding tutoring institutions for children, accompanying children when coming and going home from school, being good listeners, accompanying learning activities at home, taking children on the first day of school, meeting with teachers through parents association, and present at the distribution of learning outcomes report card.